Pengaruh Aplikasi Kehadiran dan Sistem Pelaporan Digital terhadap Kinerja Administrasi Dosen di Universitas Buana Perjuangan - Yogi Ginanjar; Undang Ruslan Wahyudi; Saepul Ma'mun; Endi Rochaendi (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This study aims to empirically evaluate the influence of the implementation of lecturer attendance applications and digital reporting systems on the improvement of administrative performance among lecturers at Buana Perjuangan University Karawang, within the broader framework of digital transformation in higher education governance. Using a quantitative approach and multiple linear regression analysis, the study reveals that both independent variables—lecturer attendance application (X₁) and digital reporting system (X₂)—have a statistically significant impact, both simultaneously and partially, on the dependent variable, namely lecturer administrative performance (Y). The research instruments demonstrate strong construct validity and high reliability (Cronbach’s Alpha > 0.8), and the regression model fulfills all classical assumptions. The key findings indicate that the digital reporting system exerts a more substantial effect than the attendance application in enhancing the efficiency, accuracy, and accountability of administrative tasks. These results affirm the relevance of the Technology Acceptance Model (TAM) and the DeLone and McLean Information System Success Model, particularly in relation to system quality, perceived usefulness, and user satisfaction. This study contributes to the existing body of knowledge on technology adoption in higher education and offers practical implications for the development of integrated, user-centered, and sustainable academic information systems as part of institutional strategies to meet the demands of digitalization in the era of the Fourth Industrial Revolution and Society 5.0.